2016
DOI: 10.1371/journal.ppat.1005398
|View full text |Cite|
|
Sign up to set email alerts
|

Blimp-1-Dependent IL-10 Production by Tr1 Cells Regulates TNF-Mediated Tissue Pathology

Abstract: Tumor necrosis factor (TNF) is critical for controlling many intracellular infections, but can also contribute to inflammation. It can promote the destruction of important cell populations and trigger dramatic tissue remodeling following establishment of chronic disease. Therefore, a better understanding of TNF regulation is needed to allow pathogen control without causing or exacerbating disease. IL-10 is an important regulatory cytokine with broad activities, including the suppression of inflammation. IL-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
156
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(170 citation statements)
references
References 87 publications
13
156
1
Order By: Relevance
“…These cells in murine and human peripheral blood can be sorted as CD4 + CD49b + LAG3 + T cells (17), enabling their recognition by FACS. This phenotype cannot be used to detect Tr1 cells by immunohistochemistry, although they can be detected by double immunological staining (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…These cells in murine and human peripheral blood can be sorted as CD4 + CD49b + LAG3 + T cells (17), enabling their recognition by FACS. This phenotype cannot be used to detect Tr1 cells by immunohistochemistry, although they can be detected by double immunological staining (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, loss of TIGIT results in hyperproliferative and inflammatory T cell responses and a marked reduction in IL-10 9,14 . IL-10 itself is a key regulator of immune responses during infections, where it plays a two-sided role by both promoting pathogen persistence [17][18][19] as well as limiting excessive Th1 and CD8 + T cell responses that cause immune pathology 20,21 . Incidentally, many chronic or latent human viruses have evolved to encode IL-10 homologs in order to evade immune control 22 .…”
mentioning
confidence: 99%
“…However, Tr1 cells were also found to contribute to IL-10 production, and another study showed that Tr1 cells were the main source of IL-10 in the spleen of VL patients 152 . We also find Tr1 cells to be the predominant source of IL-10 in murine VL 37 . It is becoming more apparent that multiple mechanisms feed into IL-10 production by Tr1 cells.…”
Section: Treg and Tr1 Cellssupporting
confidence: 57%
“…Macrophages are a relevant source of IL-10 during leishmaniasis; macrophage derived IL-10 has been demonstrated to impair parasite control in cutaneous leishmaniasis by autoregulating production of IL-12 and TNFα, which are critical for parasite clearance 177 . We also find that IL-10 prevents parasite control in VL, but protects macrophages from TNFα mediated death in a similar manner 37 . As with malaria, it may be possible to manipulate IL-10 producing cells to alter disease outcome.…”
Section: Il-10supporting
confidence: 57%
See 1 more Smart Citation